Mercury contamination levels in rivers and resident wells in Padesa and Sepukur Villages, Lantung District, Sumbawa Regency, Indonesia - Nurlaila Agustikawati; Anak Agung Ngurah Ketut Riyadi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Traditional mining business activities for processing gold ore in Lantung District are amalgamated using mercury (Hg) from 2015 to 2021 and are still ongoing. On average, there are ten to fifteen logs in each village, the waste being discharged only through ditches or small streams leading to rivers. Mercury that enters the aquatic environment will experience precipitation, dilution, and dispersion, absorbed by organisms living in these waters. Mercury water will be converted into methyl mercury by certain bacteria called biomethylation. In methyl-mercury (MeHg), mercury has toxic properties, firm binding, and high solubility. If consumed by biota, it will experience bioaccumulation in the body, and if consumed by humans for a long time, it can cause various types of diseases up to death. This study aims to determine mercury levels in the rivers and wells of residents in Sepukur Village and Lantung District. The research method is a survey with a sampling technique that is purposive sampling based on the distance from the logs to the residents' wells and rivers. The results showed that mercury levels in the Padesa Village river and springs were 0.002 mg/L. The average mercury level in the Sepukur Village River is 0.0004 mg/L, dug wells are 0.0014 mg/L, and drilled wells are 0.0024 mg/L. It can be concluded that the mercury levels in the springs in the village of Sepukur exceed the standard, and the river is classified in class 3. Mercury levels in the drilled wells of the residents of Sepukur Village exceed the standard, and the dug wells are still within the safe limits of the standard. Meanwhile, the river level in the Village of Sepukur is still relatively safe.